Development of Digital Circuits Learning Media Using Articulate Storyline with the 4D Model - M. Zikrul Ansori; Delsina Faiza; Thamrin; Efrizon (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
Education plays a vital role in developing students' potential. With the advancement of Information and Communication Technology (ICT), innovations in education have evolved, particularly in creating more effective, inspiring, and motivating media, methods, and learning strategies. This research aims to develop a learning media using Articulate Storyline for the "Digital Circuits" material, targeting 11th-grade students in the Industrial Electronics Engineering program at SMK Negeri 1 Padang. The Research and Development (R&D) method used the 4-D development model: Define, Design, Develop, and Disseminate. Validation by two material experts resulted in a score of 91.67%, categorized as "Very Valid," while media validation achieved an average score of 94.16%, also rated as "Very Valid." A practicality test with 15 students indicated a practicality rate of 87.90%, categorized as "Very Practical." These results suggest that the developed learning media is feasible for use in the classroom and effective in enhancing students' learning experiences.